2014
DOI: 10.1177/239700221402800110
|View full text |Cite
|
Sign up to set email alerts
|

Leaders Enhance Group Members' Work Engagement and Reduce Their Burnout by Crafting Social Identity

Abstract: Previous research has examined burnout and work engagement as a function of demands and resources at work. Yet we know little about the ways in which these are determined by people's social experience as a member of their workgroup as shaped, in particular, by leaders' management of shared identity. To address these issues, we propose a model in which leaders' identity entrepreneurship (the degree to which the leader promotes understanding of shared group identity) impacts on group performance through burnout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
86
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(96 citation statements)
references
References 103 publications
(142 reference statements)
9
86
0
1
Order By: Relevance
“…Our findings indicate that, with regard to promoting higher rates of attendance in sport and exercise sessions, leaders are effective when they are perceived to behave in a way that demonstrates their capacity to create , represent , advance , and embed an identity that is shared by the particular group they lead. In other words, our findings extend growing evidence from other domains for the value of leaders engaging in identity leadership . As such, they add to growing evidence for the benefits of favorable group environments for promoting physical activity, and further demonstrate the impact of social factors on individuals' physical activity behaviors .…”
Section: Perspectivessupporting
confidence: 82%
See 2 more Smart Citations
“…Our findings indicate that, with regard to promoting higher rates of attendance in sport and exercise sessions, leaders are effective when they are perceived to behave in a way that demonstrates their capacity to create , represent , advance , and embed an identity that is shared by the particular group they lead. In other words, our findings extend growing evidence from other domains for the value of leaders engaging in identity leadership . As such, they add to growing evidence for the benefits of favorable group environments for promoting physical activity, and further demonstrate the impact of social factors on individuals' physical activity behaviors .…”
Section: Perspectivessupporting
confidence: 82%
“…Second, the current findings extend the growing body of evidence that highlights the benefits of identity leadership both within and outside the sport and exercise domain. Most notably, findings build upon growing evidence concerning (a) the positive relationship between identity leadership and group members' health and well‐being in organizational settings, and (b) the positive relationship between identity leadership and group members' performance in sporting settings . Bridging the gap between these two lines of research, the current findings are the first to reveal a positive relationship between identity leadership and health‐related outcomes in sport and exercise settings.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Finally, our research contributes to the consumer ethics literature by investigating the linkage between the social identity and social exchange perspectives as shaped by customers' CSR perceptions and customer citizenship behaviour. The findings suggest that a sense of “we‐ness” (i.e., identification) (Steffens, Haslam, Kerschreiter, Schuh, & van Dick, ), such as customer‐company identification generated from a company's CSR, combined with affective commitment toward the company, is relevant in increasing customer citizenship behaviour. This has important implications for the literature on consumer ethics.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed a negative relationship between job satisfaction and employee burnout (Maher & El-Bedawy, 2014;Steffens, Haslam, Kerschreiter, Schuh, & Van Dick, 2014;Wang, Zheng, Hu, & Zheng, 2014). Job satisfaction reflects the degree to which a person's needs, or expectations are met at work and represents the degree of satisfaction with one's work, co-workers, supervisors, promotional opportunities, pay scale, and organizational setup.…”
Section: The Employee Burnout Phenomena: Job Burnout and Job Stressmentioning
confidence: 99%